The Development of Flash Interactive Learning Media in Improving English Speaking Skills of Grade X at SMA Negeri 16 Medan - Suyono Suyono; Naeklan Simbolon; Dina Ampera (BIRCU, 2021)
The purpose of this research is to know about: (1) feasibility of flash interactive learning media used by English teachers in speaking skills of grade X at SMA Negeri 16 Medan of Academic Year 2019/2020; and (2) the effectiveness of flash interactive learning media in improving English speaking skills of grade X at SMA Negeri 16 Medan of Academic Year 2019/2020. The research method is the Bord and Gall development model with the learning design of the Dick and Carey Model, consisting of 2 stages: (1) Stage I, namely: conducting preliminary research, making software design, collecting materials, making and producing products, product field testing, and product effectiveness test; and (2) Stage II, product effectiveness test by: normality test, linearity test, hypothesis test, and calculating the value of media effectiveness. Subjects consisted of 64 students of grade X. For the development of products using 2 experts of instructional design, 2 materials experts, 2 software experts, 3 students tested one by one, and 9 small groups classes students. Limited field test shows: (1) the average percentage of the results of the assessment of English-speaking skills by material experts is 79.7%; (2) the average percentage of English-speaking skills assessment results by learning design experts is 86%; and (3) the average percentage of English-speaking skills assessment results by software experts is 80.1%. The results were obtained tcount > ttable (11.315 > 1.69), which concluded that Ho refused and Ha is received, so that it can be stated that there are significant and significant differences between the English-speaking skills of students taught using interactive learning media (82,969) and the average English-speaking skills of students taught using conventional learning media (62,594) can be accepted and tested for truth.